The saint eaudiobook Original sinners: the white years series, book 1. - Reisz, Tiffany (The Original Sinners, 2014)
Rebellious, green-eyed Eleanor never met a rule she didn't want to break. Sick of her mother's zealotry and the confines of Catholic school, she declares that she'll never go to church again. But her first glimpse of beautiful, magnetic Father Marcus Stearns—Søren to her and only her—and his lust-worthy Italian motorcycle is an epiphany. Eleanor is consumed, yet even she knows that being in love with a priest can't be right. But when one desperate mistake nearly costs Eleanor everything, it is Søren who steps in to save her. When she vows to repay him with complete obedience, a whole world opens before her as he reveals to her his deepest secrets. Danger can be managed—pain, welcomed. Everything is about to begin Contains mature themes.